2022
DOI: 10.3389/fcell.2022.871512
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-related gene signatures in neuroblastoma associated with prognosis

Abstract: Background: Ferroptosis, a form of regulatory cell death, has been linked to the development of various tumors. Peripheral neuroblastoma (NB) is one of the most common extracranial solid tumors in children, and it has been proposed that regulating tumor cell ferroptosis may be a future treatment for NB. However, it is unclear how ferroptosis contributes to NB development.Methods: Expression data were collected from two independent cohorts (GEO and Arrayexpress databases). Univariate Cox analysis, multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…This pathway, by which extracellular iron uptake occurs, affects homeostasis of the labile iron pool. In a study on ferroptosis-related gene signatures associated with prognosis in neuroblastoma, STEAP3 was found to be highly expressed ( 43 ), and increased STEAP3 activity undoubtedly increased the amount of labile iron. Another study found that higher levels of STEAP3 expression in gliomas were associated with worse prognosis for patients and promoted the proliferation and self-renewal of glioma stem cells ( 44 ).…”
Section: Iron Metabolism In Cscsmentioning
confidence: 99%
“…This pathway, by which extracellular iron uptake occurs, affects homeostasis of the labile iron pool. In a study on ferroptosis-related gene signatures associated with prognosis in neuroblastoma, STEAP3 was found to be highly expressed ( 43 ), and increased STEAP3 activity undoubtedly increased the amount of labile iron. Another study found that higher levels of STEAP3 expression in gliomas were associated with worse prognosis for patients and promoted the proliferation and self-renewal of glioma stem cells ( 44 ).…”
Section: Iron Metabolism In Cscsmentioning
confidence: 99%